An overview of spinal injuries in children: Series of 122 cases - Singh, Ajit; Goyal, Nishant; Gupta, Deepak Kumar; Mahapatra, Ashok Kumar (Indian Journal of Neurotrauma, 2011)
Spinal injuries are rarely seen in children. We retrospectively analyzed 122 consecutive cases of severe spinal injuries in children (age<20 years). Clinically, 31% sustained complete spinal cord injuries, 19% were neurologically intact and 50% had incomplete injuries. Fall was the most frequent cause of injury, followed by road traffic accidents (RTAs). Seventy three cases (60%) involved cervical spine, 22 cases (18%) involved dorsal spine and 27 cases (22%) involved lumbo-sacral spine. The upper cervical spine was more commonly injured in younger children and the lower cervical and dorso-lumbar spine was involved more often in older children. Fracture alone and fracture associated with subluxation were seen in equal frequency (50% each). Spinal cord injury without radiological abnormality was seen in two cases only. About two third of the cases were managed surgically while one third were managed conservatively. In-hospital mortality was less than 5 %. Four out of eight patients with hypotension at presentation expired (p value < 0.001). The mortality in patients with Frankel grade A injury was 5 out of 38 patients (13%), as compared to a single mortality seen in the rest of the study patients (1%) (p value- 0.011). There was no association of the outcome with the age of the patient. Patients with associated severe head injury had worse outcome (p value − 0.123). Patients who were managed surgically had a significantly lower mortality (1%), as compared to those managed conservatively (13%) (p value- 0.011). While fall remains the major cause of spinal injuries in children, RTA is fast emerging as a leading cause. Upper cervical spinal injuries are commoner in younger children, while the incidence of injuries in lower cervical and dorso-lumbar spine increases with age. Hypotension, complete neurological injury at presentation and associated severe head injury are the factors associated with higher in-hospital mortality.
Keywords: children; Frankel; Spinal injury; outcome